Innovation and immigration: Insights from a placement policy - Vera Jahn; Max Friedrich Steinhardt (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2016)
The paper examines the impact of immigration on innovation. We exploit an immigrant placement policy which took place during the early nineties in Germany when large numbers of so called ethnic Germans entered the country. This allows us to overcome the potential bias of endogenous location decisions and to estimate how regional inflows of ethnic Germans affected patent applications over time. Although the majority of ethnic German inflows was unskilled, we do not find any evidence of a negative impact on innovations. Instead, our panel estimates suggest that immigration had no or even a positive impact on innovations.
Keywords: F22; O32; R11; 330; Innovation; Immigration; Ethnic Germans; Quasi-experimental setting